Endoscopic findings of acid peptic disease at low and high altitude: Kathmandu versus Rasuwa districts of Nepal (Journal of Patan Academy of Health Sciences, 2022)
Introduction: Features of Acid Peptic Disease (APD) have specific presentations from low to high altitudes. This study aims to compare the endoscopy findings of APD at low altitudes (Kathmandu Valley) and High Altitudes (Rasuwa District) of Nepal.Method: Endoscopy findings of APD patients from Nov 2017 to Dec 2021 at Manmohan Medical College and Teaching Hospital (MMTH) were reviewed from the data kept in the endoscopy unit to compare the findings in patients from low altitudes (Kathmandu valley) and high altitudes (Rasuwa district). Variables included were age, sex, and endoscopy findings of APD. Microsoft Excel was used for data analysis. Chi-square analysis was used for the association between APD findings and altitude. A p-value ≤0.05 was considered statistically significant.Result: Out of 2937 APD patients, 1560 (53.1%) were male and 1377(46.9%) female, age 48.5 years (range 16-81) with 2701(91.6%) having endoscopic findings of APD. Among 2701 APDs, 1448 (88.6%) were from the low altitude of Kathmandu valley, and 1253 (96.2%) from high altitude (Rasuwa district), p-value